2019
DOI: 10.22270/jddt.v9i2.2494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preliminary phytochemical screening, acute toxicity and antioxidant profile of Ocimum kilimandscharicum

Abstract: Nature has offered us diverse curative herbs having with powerful antioxidant phytochemicals. Ocimum (Lamiaceae) is a notable source of volatile oils and flavouring agents in general and primarily of eugenol, methyl eugenol, linalool, methyl chavicol, etc. Karpoora Thulasi is a member of this genus; nevertheless, not much literature has been reported on its safety and antioxidant potential. In this investigation, we did a pre-clinical safety assessment of concentrate of O. kilimandscharicum on Sprague Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Plants are rich in secondary metabolites which usually facilitate the synthesis of silver nanoparticles. In a research study conducted by Saxena et al [33], flavonoids, alkaloids, glycosides, saponins, and tannins were present in methanolic extract of O. kilimandscharicum .…”
Section: Resultsmentioning
confidence: 99%
“…Plants are rich in secondary metabolites which usually facilitate the synthesis of silver nanoparticles. In a research study conducted by Saxena et al [33], flavonoids, alkaloids, glycosides, saponins, and tannins were present in methanolic extract of O. kilimandscharicum .…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants in medicinal plants play a major role in the defense against oxidative damage caused by reactive oxygen species [7,52]. erefore, the total antioxidant activity of the four selected extracts of A. moschatus was assessed by DPPH radical scavenging assay.…”
Section: Dpph Scavenging Activitymentioning
confidence: 99%
“…erefore, the total antioxidant activity of the four selected extracts of A. moschatus was assessed by DPPH radical scavenging assay. It is a simple, rapid, and relatively inexpensive assay, widely used in the evaluation of the antioxidant potential of aqueous or organic extracts with hydrophilic and lipophilic compounds [7,53]. e total antioxidant activity is expressed in terms of IC 50 ( Table 5).…”
Section: Dpph Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Vero cell lines show that the tissue culture toxicity dose is 500 µg mL −1 for the methanol and aqueous extract of this plant. [ 27 ] Leaf extracts obtained using methanol have undergone preclinical safety assessment in Sprague Dawley pathogen‐free rats and this showed that the rats can tolerate up to 2500 mg kg −1 of the extract without any significant adverse effects like tremors, coma, and fatality. [ 28 ] Essential oils present in the leaves have been hydrodistilled and this is found to inhibit the proliferation of tumor cells with a GI50 of 31.90 mg mL −1 .…”
Section: Introductionmentioning
confidence: 99%